Earthworm invasion shifts trophic niches of ground-dwelling invertebrates in a North American forest. (August 2022) - Ferlian, Olga; Cesarz, Simone; Lochner, Alfred; Potapov, Anton; Thouvenot, Lise; Eisenhauer, Nico
Abstract: Earthworms are invading soil communities worldwide, and their actions as decomposers and ecosystem engineers are vastly impacting many ecosystem functions. In the northern regions of North America, invasive earthworms are often functionally distinct from the native invertebrate fauna and, thus, typically occupy empty trophic niches in soil food webs. Nevertheless, they can affect the co-occurring soil invertebrate communities in multiple indirect ways. Particularly, the redistribution and removal of litter resources can affect feeding interactions of soil biota that channel up to higher trophic levels, such as predators, causing shifts across all components of the soil food web, which are hard to investigate. To study trophic shifts in earthworm-invaded soil communities, we used ground predators as model organisms since they occupy high trophic levels and connect different energy channels in soil food webs. We used stable isotope ( 13 C and 15 N) and fatty acid analyses as complementary tools to describe the trophic levels and basal resources of consumers that were impacted by earthworm invasion, specifically examining the trophic niches and resources available to ground-dwelling invertebrates of a northern aspen forest. The distinct trophic niches of invertebrate species were affected significantly by earthworm invasion. Shifts in neutral lipid fatty acid profiles as well as decreases in animal Δ 13 C and Δ 15 N signatures indicated changes in basal resources and trophic levels, respectively. Furthermore, we observed a trend of greater intra-specific and less inter-specific variation in fatty acid profiles of soil organisms following earthworm invasion. Notably, shifts in marker fatty acids of ground-dwelling invertebrates were opposite to the changes observed in soil microbial communities, suggesting de-coupling of soil microbial and ground arthropod food-web compartments. Overall, our study revealed a systemic effect of invasive earthworms on ground-dwelling invertebrates. Earthworms presumably consumed a considerable amount of resources, such as litter and, thus, incorporated them in the soil food web, which was, as a basal resource, not available in the food web free of earthworms. Overall, the ground-dwelling invertebrates have adapted (changed their trophic function) which could explain the balancing of potential environmental changes that are caused by invasive earthworms. This observation potentially explains why these species are dominant in the studied forest and resist earthworm invasion. Future studies should investigate if altered litter availability also causes shifts in soil biodiversity in invaded forests, which is assumed but rarely directly tested to date. Highlights: Earthworms are invading soil communities worldwide with vast impacts on ecosystems. We investigated trophic niches in soil communities with earthworm invasion. We combined stable isotope and fatty acid analyses as complementary tools. We found that earthworms incorporated litter resources in the soil food web. Intra-specific variation in niches increased and inter-specific variation decreased.